İnflammatory pseudotumor of the liver: clinical and pathological features of two patients - Semin AYHAN,; Funda YILMAZ,; Gül YÜCE,; Yıldıray YÜZER,; Ahmet MEMİŞ,; Ali MENTEŞ, (Turkish Journal of Gastroenterology, 2019)
-